Disability in the elderly in terms of public health - Yigitbas, Cagla; Deveci, S. Erhan (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2016)
Elders frequently are defined as persons aged 65 years and over. All populations around the world are seeing increasing numbers of elders. Elders' physiological, biological, emotional, chronological and functional properties accommodate it to specific problems. Growing numbers of older citizens worldwide cause to seek new solutions on their families, communities, and countries, including increased needs for health care, in-home care-giving, and appropriate housing. On the other hand, some of the functions and social relations decrease with aging regarding physical and psychological aspects. Increased disability rate among the elderly is becoming one of the common problems. Disability is a significant issue for today's society with major social and economic consequences. Also it has become a significant financial burden in the country as well as the effects on society. So the purpose of this review is to address aging and disability issues from the conceptual point of view of public health. Key words: Public health, elderly, disability
Halk sağliği açisindan yaşlilarda yeti yitimi
Keywords: Public health; elderly; disability